Hyposmolality stimulates apical membrane Na(+)/H(+) exchange and HCO(3)(–) absorption in renal thick ascending limb - Watts, Bruns A. (American Society for Clinical Investigation, 1999)
The regulation of epithelial Na(+)/H(+) exchangers (NHEs) by hyposmolality is poorly understood. In the renal medullary thick ascending limb (MTAL), transepithelial bicarbonate (HCO(3)(–)) absorption is mediated by apical membrane Na(+)/H(+) exchange, attributable to NHE3. In the present study we examined the effects of hyposmolality on apical Na(+)/H(+) exchange activity and HCO(3)(–) absorption in the MTAL of the rat. In MTAL perfused in vitro with 25 mM HCO(3)(–) solutions, decreasing osmolality in the lumen and bath by removal of either mannitol or sodium chloride significantly increased HCO(3)(–) absorption. The responses to lumen addition of the inhibitors ethylisopropyl amiloride, amiloride, or HOE 694 are consistent with hyposmotic stimulation of apical NHE3 activity and provide no evidence for a role for apical NHE2 in HCO(3)(–) absorption. Hyposmolality increased apical Na(+)/H(+) exchange activity over the pH(i) range 6.5–7.5 due to an increase in V(max). Pretreatment with either tyrosine kinase inhibitors or with the tyrosine phosphatase inhibitor molybdate completely blocked stimulation of HCO(3)(–) absorption by hyposmolality. These results demonstrate that hyposmolality increases HCO(3)(–) absorption in the MTAL through a novel stimulation of apical membrane Na(+)/H(+) exchange and provide the first evidence that NHE3 is regulated by hyposmotic stress. Stimulation of apical Na(+)/H(+) exchange activity in renal cells by a decrease in osmolality may contribute to such pathophysiological processes as urine acidification by diuretics, diuretic resistance, and renal sodium retention in edematous states. J. Clin. Invest. 104:1593–1602 (1999).